3x+6x=-15+6x

Simple and best practice solution for 3x+6x=-15+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+6x=-15+6x equation:


Simplifying
3x + 6x = -15 + 6x

Combine like terms: 3x + 6x = 9x
9x = -15 + 6x

Solving
9x = -15 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
9x + -6x = -15 + 6x + -6x

Combine like terms: 9x + -6x = 3x
3x = -15 + 6x + -6x

Combine like terms: 6x + -6x = 0
3x = -15 + 0
3x = -15

Divide each side by '3'.
x = -5

Simplifying
x = -5

See similar equations:

| 5x+1-4=x+7 | | y=19x^2+9x+7 | | -40=8(4p-8)-8(3+2p) | | 3x^3+x^2+6x+2=0 | | 2b+2-5b+b=180 | | 0.05x^2+1.1x=200 | | 300+0.70x=40+0.90x | | (x-14)2= | | 6+2(3j-2)=49(1+j) | | 4a^2-10a=0 | | 69.1=2*3.14*r | | 7-3(a+4)= | | t^2-7=18 | | 6y^3-21y^2-4y+14=0 | | -9=-5(8-2k)+3(k-7) | | 5x-20=10x+15 | | -5(3a+6)=-105 | | 9y=7y+24 | | 5+4t=7(t) | | -16x^2+60x=56 | | 4a+3(a-2)=2(3a-2) | | 2(4x+3)+4=3x(2x+4) | | 3(x-2)=9(9x+2) | | (-8+5i)(-7+3i)= | | 15-3(2x-9)+x=115 | | -16x^2+6x=56 | | 69.1=3.14*r | | 0.06(y-9)+0.20y=0.16y-0.01(60) | | -6.1x+108.8= | | 6(5n+7)-4(4n+6)=-24 | | 5+4n=7+n | | 4y+2+y=180 |

Equations solver categories